ANALISIS PERSEPSI KARYAWAN TERHADAP KEPEMIMPINAN DAN LINGKUNGAN KERJA PADA PERUSAHAAN STARTUP BERDASARKAN ULASAN MEDIA DIGITAL GLASSDOOR - Mardiman Mardiman; Hening Lintang Kinanthi; Muhammad Fachmi (Politeknik Negeri Lhokseumawe, 2026)
This study aims to analyze employee perceptions of leadership and work environment in startup companies by utilizing review data from the Glassdoor platform. The research employs a descriptive qualitative approach with content analysis of 500 employee reviews from five leading technology startups during the 2020-2024 period. Results indicate that transformational leadership style has a significant positive correlation with employee satisfaction, evidenced by keywords such as vision, transparent, and supportive appearing in high-rated reviews. Conversely, micromanagement and one way communication emerge as primary causes of dissatisfaction in low rated reviews. Flexible work environments are perceived positively but may lead to burnout if work-personal boundaries are not clearly managed. Senior Leadership rating serves as the strongest predictor of employee recommendation (recommend to a friend), surpassing financial compensation factors. Digital review data proves valid as a real-time diagnostic tool for organizational climate with minimal social desirability bias. This study concludes that leadership transparency and authentic work life balance management are key factors in building positive employer branding in the digital era.Keywords: Leadership, Work Environment, Startup, Glassdoor, Employee Perception